2008
DOI: 10.1016/j.bbamcr.2008.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The anti-apoptotic activity associated with phosphatidylinositol transfer protein α activates the MAPK and Akt/PKB pathway

Abstract: The conditioned medium (CM) from mouse NIH3T3 fibroblast cells overexpressing phosphatidylinositol transfer protein alpha (PI-TPalpha; SPIalpha cells) demonstrates an increased anti-apoptotic activity compared with CM from wild type NIH3T3 (wtNIH3T3) cells. As previously shown, the anti-apoptotic activity acts by activating a G protein-coupled receptor, most probably a cannabinoid 1 (CB1)-like receptor as the activity was blocked by both pertussis toxin and rimonabant [M. Schenning, C.M. van Tiel, D. Van Manen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…ERK signaling pathway is one of the three mitogenactivated protein kinase (MAPK) cascades that play important roles in the regulation of cell proliferation, differentiation and survival. Evidence shows that phosphorylated ERK may phosphorylate a variety of substrates and promote cell survival (5,31,53). The present results suggested that NGF-activated TrkA mediated Akt and ERK phosphorylation, which could promote neuronal survival against oxidative damage.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…ERK signaling pathway is one of the three mitogenactivated protein kinase (MAPK) cascades that play important roles in the regulation of cell proliferation, differentiation and survival. Evidence shows that phosphorylated ERK may phosphorylate a variety of substrates and promote cell survival (5,31,53). The present results suggested that NGF-activated TrkA mediated Akt and ERK phosphorylation, which could promote neuronal survival against oxidative damage.…”
Section: Discussionsupporting
confidence: 57%
“…Both Akt/PKB and ERK/MAPK are of tremendous importance for several neuronal key signaling events, including cell differentiation, proliferation and survival (53). In the present study, we investigated whether these pathways were involved in brain protection effects of troxerutin.…”
Section: Troxerutin Protects Mouse Brain Agaisnt D-gal Neurotoxicity mentioning
confidence: 96%
“…Data are expressed as mean AE SD from three independent experiments performed in triplicate. Results showing statistically significant differences from control: *p < 0.05 and ***p < 0.001. phosphatidylserine synthases, phosphatidylinositol transfer protein alpha and anti-apoptotic protein BCL-xL (Chaturvedi et al, 2004;Rochette and Brash, 2008;Schenning et al, 2008;Yu et al, 2004). There are no reports of overexpression of these molecules in P388D1 macrophages.…”
Section: Resultsmentioning
confidence: 93%
“…fibroblasts, Chinese-hamster ovary cells and keratinocytes (Carvalho et al, 2008;Chaturvedi et al, 2004;Rochette and Brash, 2008;Schenning et al, 2008;Yu et al, 2004). This resistance is related to the overexpression of Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Recent studies have reported that CB 1 inhibition in human peripheral blood mononulclear, human breast cancer cells, and NIH3T3 fibroblasts results in inhibition of the cell proliferation and migration and/or apoptosis mediated via inhibition of ERK1/2 and interrelated signaling pathways [20] [21] [22] [23]. CB 1 inhibition also attenuates doxorubicin-induced cell death in cardiomyocytes, which may also involve ERK1/2 activation [24].…”
Section: Discussionmentioning
confidence: 99%